Germany and the Baltic problem after the Cold War : the development of a new Ostpolitik, 1989-2000 - Spohr Readman, Kristina (Routledge, 2004)
The root question this book addresses is how the new Germany will use its re-found status as a great power. In seeking an answer, Kristina Spohr Readman scrutinises Germany's new Ostpolitik (eastern policy) in the period 1989-2000.